Design of Performance management System in Non-Profit Organisation Based on Integrated Performance Management System Framework - Inggis, Raka Achmad; Wibisono, Dermawan (Journal of Business and Management, 2016)
Abstract- Rumah Kepemimpinan, as a Non-Profit Organisation, has been running for more that a decade, however, they face the same problem regarding to their performance every year. They have a problem in reaching their annual donation inflow target and they seem that they cannot overcome the problem. It was finally found that they do not have a good performance management system. Therefore, this research is conducted to identify the performance variables that help Rumah Kepemimpinan to improve their organisationâ€™s performance. There are three research objectives in this paper, analyse the current vision and mission of Rumah Kepemimpinan to meet the criteria of good vision and mission, identify the new strategies for Rumah Kepemimpinan, and identify the Performance Variables of RK in 2016 based on IPMS Framework. The method used to develop the performance management system is by analysing the vision and mission, assessing the current external and internal condition, identifying the critical success factors, and defining the performance variables based on IPMS Perspective. The data is gathered by discussion with the management, explore information through internet and look to the internal document of Rumah Kepemimpinan. The data analysis shows that the vision and mission of Rumah Kepemimpinan has met the criteria of good vision and mission. The current external-internal condition assessment shows that Rumah Kepemimpinan should apply the â€œHold and Maintainâ€ strategy. The discussion with the management and analysis of current external-internal condition of Rumah Kepemimpinan are resulting sixteen Critical Success Factors (CSFs). They are the factors which determine the success of Rumah Kepemimpinan. The CSFs are broken down into performance variables. There are forty-three performance variables that have been identified. By having new performance variables that represents the current condition and align to the vision, Rumah Kepemimpinan will be on the right track in reaching their vision.Â Keywords: Performance Management System, Integrated Performance Management System Framework, Non-Profit Organisation, Rumah Kepemimpinan, Critical Success Factors, Performance Variablesâ€ƒ